Exploring The Triad of Sleep, Pain and Mental Health in Adolescent Idiopathic Scoliosis: A Systematic Review - Marsella Ayudya Maharani; Aditya Denny Pratama (Utan Kayu Publishing, 2026)
Adolescent Idiopathic Scoliosis is a prevalent spinal deformity linked to back pain, psychosocial burden, and diminished quality of life. Recent evidence indicates that sleep disturbances represent a significant comorbidity in this population. This systematic review synthesises current findings on the prevalence of sleep disturbances, associated factors such as pain and mental health, and their impact on quality of life among adolescents with idiopathic scoliosis. The review followed PRISMA 2020 guidelines. A systematic search of PubMed, Scopus, and Google Scholar identified studies published from January 2020 to October 2025. Ten studies met the inclusion criteria, comprising six cross-sectional, two case-control, one pilot, and one qualitative study, with sample sizes ranging from 11 to 19,315 participants. The prevalence of poor sleep quality ranged from 64.8% to 75.5%. Back pain and depressive symptoms were consistently associated with sleep disturbances. Short sleep duration (less than 8 hours) emerged as a potential risk factor, while brace treatment was associated with poorer sleep outcomes. Evidence also suggested an increased risk of sleep-disordered breathing. Overall, sleep disturbances, pain, and psychological distress frequently co-occur and are associated with reduced quality of life. However, these conclusions should be interpreted with caution, as no formal quality assessment of the included studies was performed.